Dichotomies in Understanding of Peace in Nepal - Timalsina, Rajib (Journal of APF Command and Staff College, 2021)
In Nepal, the decade long armed conflict between 1996 and 2006 has become the buzz word in most social sciences literatures. Since 2007, ‘peace’ has emerged as essential component of the academic courses and training manuals. Against this backdrop, this paper focuses on the understanding of “Peace” in local context of Nepal. This paper compares the various definitions of peace from western and eastern intellectual perspectives, examines the literatures on how they depict Nepal’s peace process, and includes a brief history of peace studies as discipline in Nepal. Methodologically, this is a reflection based paper evolved from qualitative eclectic approach. The researcher has used axial coding and domain analysis. This paper concludes that the epistemological roots of conflict and peace studies are under-researched in Nepali context. The influence of Maoist armed conflict is very dominant in peace studies literatures which have missed to produce the comparative-historic indigenous writings on Nepal.